Mg2nni0.5co0.5compound Obtaining by Mechanical Alloying and Their Performance on Hydriding Process [Obtención del Compuesto Mg2ni0.5co0.5mediante Aleado Mecánico y Estudio de Su Comportamiento Frente Al Proceso de Hidruración] - Ordonez, S; Serafini, D (Universidad Nacional de Colombia, 2017)
This work presents the microstructural evolution of mechanically alloyed Mg2Ni0.5Co0.5and a study of its hydriding properties. Mg, Ni, and Co elemental powders (atomic ratios of 2:0.5:0.5, respectively) were mechanically alloyed in a Spex 8000D high-energy mill for 36 h (amorphous sample) and subsequently submitted to a thermal treatment at 673 K for 15 min (nanocrystalline sample). The characterizations of the samples were performed with X-ray diffraction. A Sievert-type volumetric hydriding process was done at 363 K and with hydrogen pressure of 2 MPa. Desorption process was evaluated through differential scanning calorimetry. Based on the obtained results, it is possible to conclude that the amorphous structure absorbs more hydrogen, reaching a maximum of 3.6 wt. % H. Desorption process events depend on amorphous or nanocrystalline states. © The author; licensee Universidad Nacional de Colombia.